2007
DOI: 10.1111/j.1556-4029.2007.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Collembola of the Grave: A Cold Case History Involving Arthropods 28 Years After Death

Abstract: This report describes a cold case in which a cadaver of a 28-year-old female was exhumed in February 2005 from a cemetery in Battle Creek, Michigan. She had sustained a gunshot wound to the head and was found dead in her home on November 15, 1977. The body of the victim was subsequently embalmed and then buried at a depth of 1.8 m in an unsealed casket that was placed inside an unsealed cement vault. The exhumation yielded thousands of live specimens of a single species of the order Collembola or spring tails,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
1
16
0
Order By: Relevance
“…In comparison to blow and ßesh ßy larvae, these two former species are much smaller in size, making it easier for them to maneuver through the interstitial spaces in the soil to reach a carcass (Disney 2008). CofÞn ßies have been documented colonizing remains at depths up to 1.8 m (Merritt et al 2007), so it is not surprising they are capable of colonizing a carcass at 60 cm. Other studies have found cofÞn ßy larvae on carrion buried at 30 cm during the active stage of decay (Payne and King 1968), 2 mo after death (Motter 1898), and a year after death (Mé gnin 1894).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to blow and ßesh ßy larvae, these two former species are much smaller in size, making it easier for them to maneuver through the interstitial spaces in the soil to reach a carcass (Disney 2008). CofÞn ßies have been documented colonizing remains at depths up to 1.8 m (Merritt et al 2007), so it is not surprising they are capable of colonizing a carcass at 60 cm. Other studies have found cofÞn ßy larvae on carrion buried at 30 cm during the active stage of decay (Payne and King 1968), 2 mo after death (Motter 1898), and a year after death (Mé gnin 1894).…”
Section: Discussionmentioning
confidence: 99%
“…Myriads of mites, Thysanura (now order Collembola) and dipteran puparia but no beetles nor dipteran larvae were found on a human corpse interred for 4 years only in a burial case but without coffin in a grave 3 feet deep (Motter 1898). In a more recent case, the corpse of a young female recently exhumed after 28 years yielded thousands of live Collembola together with large numbers of Acari (mites) of the family Glycyphagidae, and fly puparia (Merritt et al 2007). …”
Section: Mites Are Numerous On Carcasesmentioning
confidence: 97%
“…Similarly, mites, springtails and puparia of coffin fly, Conicera tibialis, were collected from the embalmed body of a 28 year-old female with a gunshot wound to the head. The corpse was buried at a depth of 1.8 m in an unsealed casket that was placed inside an unsealed cement vault in a cemetery in Michigan, USA (Merritt et al 2007).…”
Section: Buried Carcasesmentioning
confidence: 99%
“…Although known to colonize a human corpse at a later time of decomposition, phorids may also be present at early stages of decay [7,11,12], especially when blowflies were unable to gain access [6,11]. Unlike blowflies, they are able to move through the smallest openings or meters of soil, colonizing buried or concealed corpses and carcasses [3,4,13,14]. Last but not least, some forensically important phorid species may also occur in cases of myiasis, the infestation of living humans or animals [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Blowflies (Diptera: Calliphoridae) are usually the first and most abundant colonizers and can therefore be used as indicators of the minimal time elapsed since death. However, several cases have been reported where small flies like the minute to medium sized scuttle flies (Phoridae) were present and even dominated the fauna of the carcass [3][4][5][6][7][8][9][10]. Although known to colonize a human corpse at a later time of decomposition, phorids may also be present at early stages of decay [7,11,12], especially when blowflies were unable to gain access [6,11].…”
Section: Introductionmentioning
confidence: 99%